Examining the Loopholes in the criminal justice system of Iran and Indonesia in relation to piracy crimes - Abdul Majid Rahmanian; Mansour Talebpour; Mehrdad Raijian Asli (Jurnal Cita Hukum, 2022)
Due to the chaos caused by piracy in Indonesia, the sea areas of Southeast Asia have made the movement of ships in this area dangerous, and also in Iran, the lack of up-to-date maritime laws has made it impossible to defend Iran's rights in the waters of the region. The purpose of this research is to investigate the loopholes in the criminal justice system of Iran and Indonesia in relation to piracy crimes. This research has investigated the issue at theoretical levels by analytical-comparative method. The necessary data and information have been collected by the library method and by using books and articles. According to the investigations, the results showed that the most important common loopholes in the discussion of the maritime law of Iran and Indonesia are the lack of judges specializing in maritime affairs as well as specialized experts, disparity in the punishment of pirates, the lack of educational facilities regarding maritime law, the lack of careful and appropriate attention to the laws of the relevant conventions, which is related to maritime transportation and the lack of appropriate placement in the field of maritime law. Therefore, based on the results of the research, holding joint courses for officers, especially young officers of the navies of Iran and Indonesia, cooperation to fight maritime terrorism and piracy, information exchange with the Iranian and Indonesian navies to fight maritime terrorism and piracy, and training and exchange of lawyers and judges of maritime sciences between the two countries is suggested.